PLC-γ-Ca2+ pathway regulates axonal TrkB endocytosis and is required for long-distance propagation of BDNF signaling - Moya-Alvarado, Guillermo; Valero-Peña, Xavier; Aguirre-Soto, Alejandro; Bustos, Fernando J.; Lazo, Oscar M.; Bronfman, Francisca C. (Frontiers in Molecular Neuroscience, 2024)
Brain-derived neurotrophic factor (BDNF) and its tropomyosin receptor kinase B (TrkB) are important signaling proteins that regulate dendritic growth and maintenance in the central nervous system (CNS). After binding of BDNF, TrkB is endocytosed into endosomes and continues signaling within the cell soma, dendrites, and axon. In previous studies, we showed that BDNF signaling initiated in axons triggers long-distance signaling, inducing dendritic arborization in a CREB-dependent manner in cell bodies, processes that depend on axonal dynein and TrkB activities. The binding of BDNF to TrkB triggers the activation of different signaling pathways, including the ERK, PLC-gamma and PI3K-mTOR pathways, to induce dendritic growth and synaptic plasticity. How TrkB downstream pathways regulate long-distance signaling is unclear. Here, we studied the role of PLC-gamma-Ca 2+ in BDNF-induced long-distance signaling using compartmentalized microfluidic cultures. We found that dendritic branching and CREB phosphorylation induced by axonal BDNF stimulation require the activation of PLC- in the axons of cortical neurons. Locally, in axons, BDNF increases PLC- phosphorylation and induces intracellular Ca 2+ waves in a PLC--dependent manner. In parallel, we observed that BDNF-containing signaling endosomes transport to the cell body was dependent on PLC- activity and intracellular Ca 2+ stores. Furthermore, the activity of PLC- is required for BDNF-dependent TrkB endocytosis, suggesting a role for the TrkB/PLC- signaling pathway in axonal signaling endosome formation.